2021
DOI: 10.3390/pathogens10091143
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Phylogenetic Analysis of a Novel Tick-Borne Virus in Yunnan and Guizhou Provinces, Southwestern China

Abstract: Dabieshan tick virus (DTV) is a novel tick-borne virus with the potential to infect both animals and humans. It has been confirmed that DTV is widely distributed in Shandong and Zhejiang Provinces. In this study, a total of 389 ticks were sampled from Honghe city of Yunnan Province and Bijie city of Guizhou Province, and then divided into 148 pools according to the location and species. QRT-PCR and nested PCR were performed to confirm the presence of DTV. The results showed a minimum infection rate of 2.43% (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Geographically, the minimum infection rate (MIR) of DBTV in ticks from Dandong city, Fengcheng city, Tieling city, and Benxi city, was 9.22% (19/206, 95% CI = 0.0579–0.1423), 6.67% (11/165, 95%CI = 0.0355–0.1192), 10% (10/100, 95%CI = 0.516–0.1804), 12.22% (11/90, 95%CI = 0.0655–0.2122), respectively ( Table 1 ). The MIR of DBTV in this research was markedly higher than in previous surveys in the Shandong, Yunnan, and Guizhou provinces of China ( Shao et al, 2020 ; Wang et al, 2021 ). This work presented positive for Severe fever with thrombocytopenia syndrome virus (SFTSV) in only four tick nucleic acid pools from Dandong City, with a total MIR of 0.71% (4/561, 95% CI = 0.0023–0.0194), which was compared to the MIR reported for SFTSV in Shandong Province which was slightly lower than previous studies ( Shao et al, 2020 ).…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Geographically, the minimum infection rate (MIR) of DBTV in ticks from Dandong city, Fengcheng city, Tieling city, and Benxi city, was 9.22% (19/206, 95% CI = 0.0579–0.1423), 6.67% (11/165, 95%CI = 0.0355–0.1192), 10% (10/100, 95%CI = 0.516–0.1804), 12.22% (11/90, 95%CI = 0.0655–0.2122), respectively ( Table 1 ). The MIR of DBTV in this research was markedly higher than in previous surveys in the Shandong, Yunnan, and Guizhou provinces of China ( Shao et al, 2020 ; Wang et al, 2021 ). This work presented positive for Severe fever with thrombocytopenia syndrome virus (SFTSV) in only four tick nucleic acid pools from Dandong City, with a total MIR of 0.71% (4/561, 95% CI = 0.0023–0.0194), which was compared to the MIR reported for SFTSV in Shandong Province which was slightly lower than previous studies ( Shao et al, 2020 ).…”
Section: Resultscontrasting
confidence: 85%
“…The RdRp phylogenetic analysis indicated that DBTV clustered closely with the Yongjia tick virus, Uukuniemi virus, and with a group of Tacheng tick viruses 2 (TcTV2) in the Uukuvirus genus, forming a separate branch ( Figure 2B ). Of these, TcTV2 is responsible for severe disease, and numerous studies have identified DBTV with such an evolutionary signature, further suggesting that DBTV may emerge as a human pathogen ( Wang et al, 2021 ; Yang et al, 2021 ; He et al, 2022 ). Furthermore, in this research, the seven DBTV strains displayed a high degree of amino acid identity with each other, despite being the same tick species from different eastern border regions of Liaoning Province.…”
Section: Discussionmentioning
confidence: 99%
“…It exists in several provinces in southern China. DTV genetically clustered into a branch of the Yongjia tick virus ( Li et al, 2015 ; Shao et al, 2020 ; Zhu et al, 2020 ; Wang A et al, 2021 ; Ma et al, 2022 ). However, there was no evidence of DTV infection in humans.…”
Section: Resultsmentioning
confidence: 99%
“…As of now, the full-length coding genomes of the L and S segments of the DBTV have been published. In recent years, DBTV has been discovered in various regions of China, including Shandong ( Shao et al, 2021 ), Zhejiang ( He et al, 2022 ), Liaoning ( Yang et al, 2021 ), Hubei, Yunnan, and Guizhou Provinces ( Wang et al, 2021 ). Epidemiological investigations have shown that DBTV is widely disseminated in Linyi, Tai’an, Weifang, Yantai ( Ma et al, 2022 ), and Rizhao city of Shandong Province ( Shao et al, 2020 ) and phylogenetic analysis revealed distinct lineages of DBTV ( Ma et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other tick species such as Rhipicephalus microplus and R. haemaphysaloides , have also been discovered to carry DBTV ( Ma et al, 2022 ). However, researchers have failed to isolate DBTV from positive tick sample ( Wang et al, 2021 ). The available literature shows that research on ticks in DBTV transmission is scarce.…”
Section: Introductionmentioning
confidence: 99%